THE ROLE OF THE ANDALUSIAN ISLAMIC REGIME IN PROMOTING CITIZENSHIP RIGHTS (755-1091AD) - Ouarda Belkacem Layachi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to investigate the various events that occurred in the past in relation to the Islamic history and heritage of Andalusia, which is full of its promotion of the right to citizenship and the values of peaceful coexistence, intellectual tolerance and religion between Muslims, Christians and Jews under the Umayyad state and during the era of the sects (138-484 AH corresponding to 755-1091AD), which It has a fundamental relationship with the content of this study, and then its matching with current events and the violations and attacks that occur during the conflicts between cultural, religious, linguistic, ethnic and political groups in our contemporary time through the historical approach that deals with events that occurred in the past and their relationship with contemporary events by clarifying the concept of citizenship and coexistence. Peaceful, intellectual and religious tolerance, showing their importance, and the various inhumane transgressions that different minorities are subjected to, on the one hand, And highlighting the most important international efforts devoted to protecting the minimum rights of these minorities in line with the Universal Declaration of Human Rights and various international covenants, and one of our findings is that the tolerance of Islam is consistent with its principles, purposes and universality, as Islam is the largest religion that protected human rights, including the right to citizenship and peaceful coexistence, Intellectual and religious tolerance, different religions may not blossom in the world unless there is tolerance and tolerance in them that corresponds to the nature of human beings regardless of their different cultures, customs and religions.